KEPEMIMPINAN DALAM PERSPEKTIF GENDER: ADAKAH PERBEDAAN? - Kusumawati, Andriani (Profit: Jurnal Adminsitrasi Bisnis, 2007)
Since a long time, leadership considered as â€œbiologically givenâ€ â€œ. Many perspective that relate between individual ability in leading with biologic aspect that is pursuant to sex difference between men and woman. But a number of empirical finding express that woman have equal potency in leading than men. The similarity between man leader and woman leader not so surprise because what we consider to be results of biology are really reflections of culture. Sex Difference that seen in population become blurry. If there is a little difference of leadership style between woman and men, is because of emphasis that adapted by situation that expand. That mean there are some other factor which have non-stereotype character, and gender is not its cause.Keywords: Leadership, Gender Sex Difference